Analysis Of Service Quality In The Pilaton Religious Affairs Office Of Kaliangkrik District - Ahmad Farhan Fasya; Purwanto; Nailatul Muna (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This research will conduct a qualitative descriptive analysis based on the SERVQUAL framework at the Pilot Religious Affairs Office in Kaliangkrik District. Kaliangkrik District was chosen as the research location because it reflects the dynamics of urban development, which represents challenges in providing optimal services. This research uses a descriptive qualitative approach. Research data was collected using observation and interviews. The research sources were the head of the KUA, employees, and the community. The results of this research show positive aspects of KUA services, such as the responsiveness of officers to community needs, clarity of service procedures, and efforts to maintain the cleanliness and tidiness of the office. However, several areas were also identified that required further attention, such as improvements in the provision of information and maintenance of the physical condition of facilities.